Clays and Clay Minerals, Vol. 59, No. 2, 107–115, 2011. - Cristiano, Elena; Hu, Yung-Jin; Siegfried, Matthew; Kaplan, Daniel; Nitsche, Heino (My University, 2011)
Contaminant-transport modeling requires information about the charge of subsurface particle surfaces. Because values are commonly reused many times in a single simulation, small errors can be magnified greatly. Goethite (a-FeOOH) and pyrolusite (b-MnO2) are ubiquitous mineral phases that are especially contaminant reactive. The objective of the present study was to measure and compare the point of zero charge (PZC) using different methods. The pyrolusite PZC was measured with three methods: mass titration (MT) (PZC = 5.9C0.1), powder addition (PA) (PZC = 5.98C0.08), and isoelectric point, IEP (PZC = 4.4C0.1). The IEP measurement was in agreement with literature values. However, MT and PA resulted in a statistically larger PZC than the IEP measurement. The surface area of pyrolusite, 2.2 m2g-1, was too small to permit PZC determination by the potentiometric titration (PT) method. Goethite PZC values were measured using MT (7.5C0.1), PT (7.46C0.09), and PA (7.20C0.08). The present work presents the first reported instance where MT and PA have been applied to measure the point of zero charge of either pyrolusite or goethite. The results illustrate the importance of using multiple, complementary techniques to measure PZC values accurately.
A Comparison Of Point Of Zero Charge Measurement Methodology
gsccm59201-cri.pdf-- 515KB
Keywords: Periodicals; Geology; Goethite; Pyrolusite; Point of Zero Charge; Potentiometric Titration; Mass Titration; Powder Addition; Isoelectric Point; Zeta Potential Charge; X-ray Diffraction; BET